Application of Bow-tie methodology to improve patient safety. Issue 4 (9th May 2016) - Abdi, Zhaleh; Ravaghi, Hamid; Abbasi, Mohsen; Delgoshaei, Bahram; Esfandiari, Somayeh
Abstract : Purpose: – The purpose of this paper is to apply Bow-tie methodology, a proactive risk assessment technique based on systemic approach, for prospective analysis of the risks threatening patient safety in intensive care unit (ICU). Design/methodology/approach: – Bow-tie methodology was used to manage clinical risks threatening patient safety by a multidisciplinary team in the ICU. The Bow-tie analysis was conducted on incidents related to high-alert medications, ventilator associated pneumonia, catheter-related blood stream infection, urinary tract infection, and unwanted extubation. Findings: – In total, 48 potential adverse events were analysed. The causal factors were identified and classified into relevant categories. The number and effectiveness of existing preventive and protective barriers were examined for each potential adverse event. The adverse events were evaluated according to the risk criteria and a set of interventions were proposed with the aim of improving the existing barriers or implementing new barriers. A number of recommendations were implemented in the ICU, while considering their feasibility. Originality/value: – The application of Bow-tie methodology led to practical recommendations to eliminate or control the hazards identified. It also contributed to better understanding of hazard prevention and protection required for safe operations in clinical settings.